AZ31-Mg metal matrix composite in metallurgical and testing approaches - Maryam B.H.; Sinha D.K.; Kefyalew S.; Gautam S.S.; Kumar S.; Pande S. (My University, 2025)
The objective of this research is to experimentally investigate the metallurgical, mechanical, and tribological behavior of (Formula presented.), SiC, and (Formula presented.) reinforced AZ31 magnesium metal matrix composite (MMC) fabricated via powder metallurgy process. Accordingly, the mixing of the powders was carried out through ball milling operation at various times with constant speeds. The compaction of the milled powder was carried out on hydraulic press at various compaction pressures. The improvement of the wear resistance performance at 10 and 5 vol.% SiC were revealed around 12.9% and 25.8%. The fracture mechanisms of the optimal specimen resulting from the compression test were studied under SEM observation and it revealed that both ductile and brittle fractures occurred. The results from the confirmation test revealed an improvement of 2.04 g/cm3, 13%, 110.35 MPa, and 1293.399 MPa for actual density, porosity, ultimate strength, and hardness, respectively. The uniform nature of particle distribution was observed in SEM micrograph under investigation of the microstructure of the sample. The average particle size of the sample was also obtained around 809.14 nm. The proposed material is expected to be useful for various automotive and aerospace applications precisely for pistons and wings of airplane in aerospace. © The Author(s) 2023.